Factors Related to Lifelong Learning Needs of the Elderly in Waeng Nang Sub-district, Mueang District, Maha Sarakham Province - Srithanee, Kitpapon; Kanhacha, Sasithon; Hasino, Warunyupa; Yenwattana, Yothaka (Ratchaphruek Journal, 2020)
The purposes of the research were to study the level of the requirement for lifelong learning of the elderly and to find the relationship between the personal factors of the elderly persons and the needs of lifelong learning at Waeng Nang sub-district, Mueang district, Maha Sarakham province. The sample group of the elderly who had 60 years old and above who are living in the community in total of 120 people. This was a questionnaire research. The data was analyzed by descriptive statistics; frequency, percentage, mean, and standard deviation, and chi-square test for inferential statistics. The research findings showed that; 1) the level of the needs for lifelong learning in the elderly people overall was at the middle level. When considering on the needs for each dimension subjects, it were found that the most requirements were the needs of saving, physical health and psychological health respectively, 2) the elderly factors and gender were related with the needs of lifelong learning in the mind adaption perspective, which was found significantly (p-value<0.05).Moreover, age, education level and income were also related with the needs of lifelong learning in the saving perspective was found significantly (p-value<0.05).Therefore, stakeholders who involved with the elderly’s life in community should be focus on lifelong learning management in elderly needs to develop the quality of life by emphasizing on the elderly people factors such as; sex, age, education level and income.